PENGARUH PERFORMANCE EXPECTANCY, EFFORT EXPECTANCY, DAN SOCIAL INFLUENCE TERHADAP BEHAVIORAL INTENTION PADA APLIKASI AJAIB - Siti Holipah; Rizki Syaban Mulyasaputra, Mohamad Badar Fadlilah, Shauqi Rizqulloh Mahmudi (CV. Adiba Aisha Amira, 2025)
With the rapid advancement of digital technology, technology-based investment applications like Ajaib are becoming increasingly popular. This study aims to assess the influence of Performance Expectancy, Effort Expectancy, and Social Influence on Behavioral Intention to use the Ajaib application. The research employs a quantitative method with a survey approach using Google Forms, involving 124 respondents who have experience using the Ajaib application. Data analysis is conducted using Structural Equation Modeling (SEM) with the SmartPLS software. The results reveal that Effort Expectancy and Social Influence have a significant impact on Behavioral Intention, while Performance Expectancy does not have a significant effect. Additionally, Social Influence is found to significantly influence Performance Expectancy. These findings highlight the importance of ease of use and social influence in encouraging users’ intention to adopt investment applications. The practical implications of this study suggest that app developers should focus on these factors to boost user adoption.